2017
DOI: 10.1002/14651858.cd003280.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory treatment other than corticosteroids, immunoglobulin and plasma exchange for chronic inflammatory demyelinating polyradiculoneuropathy

Abstract: Immunomodulatory treatment other than corticosteroids, immunoglobulin and plasma exchange for chronic inflammatory demyelinating polyradiculoneuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 152 publications
1
49
0
13
Order By: Relevance
“…[18][19][20] Our results confirm the safety profile of rituximab. 11,13,14 We showed that 13 out of the 16 clinically improved patients had either an improvement or a stability of the NCS parameters. Our NCS analysis is limited by the retrospective collection of the data and the heterogeneity of the tested nerves.…”
Section: Safetymentioning
confidence: 80%
See 1 more Smart Citation
“…[18][19][20] Our results confirm the safety profile of rituximab. 11,13,14 We showed that 13 out of the 16 clinically improved patients had either an improvement or a stability of the NCS parameters. Our NCS analysis is limited by the retrospective collection of the data and the heterogeneity of the tested nerves.…”
Section: Safetymentioning
confidence: 80%
“…However, there are currently no guidelines recommending a specific drug. 11 Rituximab, a monoclonal anti-CD20 antibody, has recently been used for the treatment of anti-myelin-associated glycoprotein (MAG) antibody polyneuropathy 12 and is currently used in chronic lymphoproliferative diseases and several autoimmune disorders. In CIDP, several small retrospective cohorts or single-case studies have reported possible efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Fu Liong Hiew (FLH) provided an overview of the clinical presentation and the available three evidence-based treatments for CIDP, IVIG, corticosteroids, and TPE. [28][29][30][31] He highlighted the tough decision of many clinicians in deciding first-line treatment due to combination of factors; cost, effectiveness, and side effects of treatments. Although TPE is a proven treatment for CIDP, its use is often reserved to severely disable patients not responding to other conventional first-line treatments.…”
Section: The Treatment Of Chronic Inflammatory Demyelinating Polynementioning
confidence: 99%
“…The rash gradually resolved over 2 weeks and she did not experience post-herpetic neuralgia. On day 2 of the illness, the white blood cell count was 6.04910 9 .…”
Section: Safetymentioning
confidence: 99%
“…[3][4][5][6] MMF has been used for nearly two decades in myasthenia gravis, 7,8 although its role is less clear in chronic inflammatory demyelinating polyradiculoneuropathy. 9 In central nervous system (CNS) autoimmune and immune-mediated conditions, MMF has been increasingly used in relapsing demyelinating diseases such as neuromyelitis optica spectrum disorders (NMOSD) 4,10-14 and myelin oligodendrocyte glycoprotein (MOG)-associated disease. 13,15,16 Other uses in CNS disease include autoimmune/immunemediated encephalitis 17 and cerebral vasculitis, 18 while its role is still uncertain in multiple sclerosis, [19][20][21][22] and seems to be limited in opsoclonus myoclonus ataxia syndrome.…”
mentioning
confidence: 99%